Notes recenzenta. Wokół Śmiesznego staruszka Tadeusza Różewicza we Wrocławskim Teatrze Lalek - Pułka, Leszek (2024)
A critic of a performance phenomenon is typically a flawed, imprecise observer. For instance, they may use a notebook to ensure accurate documentation of the plot, characters, strengths, and artistic merit or shortcomings of the production or acting, but they are still more complete than someone watching a recording on DVD. While the latter offers useful documentary context, it impoverishes the perception of the stage performance, stripping it of auditory, phonetic, or olfactory nuances and framing the spatiotemporal aspects of the spectacle according to the preferences of the recording's director. Both forms of communication are therefore imprecise. The first disrupts the phenomenon of seeing, breaks spatiotemporal continuity, undermines the phenomenon of co-participation, and preempts the event with prior knowledge of the text – if the critic is well-read (even when the playwright or director abandons narrative structures). The second activates processes of participation, observation, and memory that differ from those of the theater, influenced, for instance, by the popularity of speed-watching and the solitude of viewing on a screen.
Keywords: Różewicz, Tadeusz; Hejno, Wiesław